RANCANG BANGUN APLIKASI BARANG JASA MENGGUNAKAN C#, WPF, DAN SQL SERVER 2012 - Reza Kamaluddin Isman; Desi Dyah Sulistyarini; Prihatin Oktivasari (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Barang Jasa is an application that used for Divisi Pengadaan Barang dan Jasa. Barang Jasa serves to record every purchase of goods and services used to meet the needs of both fleet and crew in the long term. Barang Jasa also serves to make the Nota Dinas to be processed by Divisi Keuangan on the purchase of goods and services that have been performed. This application was created by using Windows Presentation Foundation (WPF), which is a Microsoft technology to create desktop applications. This application was made using the method protoyping development,C# as a programming language, WPF as a interface design technology, and SQL Server 2012 as the database. WPF can present the appearance that can be tailored to user needs. This study discusses the interface, backend applications, and database design. After testing the flexibility of the interface on the screen with a resolution of 1366 x 768, 1024 x 768 and 1280 x 720, proves that WPF can adjust the screen resolution being tested. The test results showed that the backend of Barang Jasa application are functioning properly, the test is done using sql query by entering the required parameters, for example username and password to log in and match the query returns results with what is displayed by the application.